ANALISIS KEBUTUHAN BAHAN AJAR KANJI TINGKAT PEMULA BERBASIS KETERAMPILAN ABAD 21 DENGAN MODEL SPD - Nia Setiawati; Dwi Astuti Retno Lestari; Eva Jeniar Noverisa (Universitas Negeri Jakarta, 2021)
The purpose of this research is to obtain the information needed so that it can describe the need for preparation of Kanji teaching materials at the beginner level based on 21st century skills for students of the Japanese Language Education Study Program FBS UNJ. This research is an exploratory descriptive study with the See, Plan, Do (SPD) model. The sample in this study was the first semester students of PSPBJ consisting of 79 peoples. This study will explain the needs of students and lecturers for kanji textbooks at the beginner level based on 21st century skills. The kanji textbooks in the Japanese Language Education Study Program UNJ are quite good in terms of appearance and content. However, students and lecturers expect more practice, especially writing exercises, so that there will be more opportunities to use kanji in sentences and discourse. Based on the situation analysis that has been done, it is necessary to have a plan to arrange kanji exercises in the form of a website or digital so that students can access them anywhere and anytime easily. This exercise is packaged in various types of questions and will present games or games so that students feel motivated to practice kanji.